2020
DOI: 10.1111/bph.15084
|View full text |Cite
|
Sign up to set email alerts
|

nNOS‐CAPON blockers produce anxiolytic effects by promoting synaptogenesis in chronic stress‐induced animal models of anxiety

Abstract: Background and Purpose Anxiety disorder is a common mental health disorder. However, there are few safe and fast‐acting anxiolytic drugs available that can treat anxiety disorder. We previously demonstrated that the interaction of neuronal NOS (nNOS) with its carboxy‐terminal PDZ ligand (CAPON) is involved in regulating anxiety‐related behaviours. Here, we further investigated the anxiolytic effects of nNOS–CAPON disruptors in chronic stress‐induced anxiety in animals. Experimental Approach Mice were intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…As expected, the gene levels of TNFα, IL‐1β, and IL‐6 in the hippocampus were appreciably elevated after LSI surgery, which were markedly attenuated by resveratrol. Aside from neuroinflammation, a reduction in the pCREB activation and BDNF expression in the hippocampus also appears to intensify anxiety‐like behaviors 31,60 . Strategies to increase pCREB activity and BDNF expression are expected to provide new approaches for suppression of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the gene levels of TNFα, IL‐1β, and IL‐6 in the hippocampus were appreciably elevated after LSI surgery, which were markedly attenuated by resveratrol. Aside from neuroinflammation, a reduction in the pCREB activation and BDNF expression in the hippocampus also appears to intensify anxiety‐like behaviors 31,60 . Strategies to increase pCREB activity and BDNF expression are expected to provide new approaches for suppression of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Given that synaptogenesis is completed within PND 20 [ 33 ], ELS may interfere with this process. Zhu et al reported that chronic mild stress-induced spine loss in dentate gyrus granule cells [ 34 ]. These findings suggest that complex developmental trauma may lead to the weakening of specific neurotransmitter systems, which resulted in reduced brain uptake of radiotracers in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, despite preclinical evidence revealing that genetic or pharmacological disruption of nNOS/NOS1AP interactions targeting an intermediate region of the dentate gyrus (and parts of CA3) has anxiolytic effects [ 13 , [68] , [69] , [70] ], there is no study linking NOS1AP to anxiety in humans. Consistent with this lack of clinical association, in the present study overexpression of NOS1AP throughout the dorsal hippocampus did not affect anxiety-related behaviours.…”
Section: Discussionmentioning
confidence: 99%